Controlling Phase Assemblage in a Complex Multi‐Cation System: Phase‐Pure Room Temperature Multiferroic (1−x)BiTi(1−y)/2FeyMg(1−y)/2O3–xCaTiO3. (5th February 2016) - Mandal, Pranab; Pitcher, Michael J.; Alaria, Jonathan; Niu, Hongjun; Zanella, Marco; Claridge, John B.; Rosseinsky, Matthew J.
Abstract : A room temperature magnetoelectric multiferroic is of interest as, e.g., magnetoelectric random access memory. Bulk samples of the perovskite (1− x )BiTi(1− y )/2 Fe y Mg(1− y )/2 O3 – x CaTiO3 (BTFM–CTO) are simultaneously ferroelectric, weakly ferromagnetic, and magnetoelectric at room temperature. In BTFM–CTO, the volatility of bismuth oxide, and the complex subsolidus reaction kinetics, cause the formation of a microscopic amount of ferrimagnetic spinel impurity, which complicates the quantitative characterization of their intrinsic magnetic and magnetoelectric properties. Here, a controlled synthesis route to single‐phase bulk samples of BTFM–CTO is devised and their intrinsic properties are determined. For example, the composition x = 0.15, y = 0.75 shows a saturated magnetization of 0.0097 μ B per Fe, a linear magnetoelectric susceptibility of 0.19(1) ps m −1, and a polarization of 66 μC cm −2 at room temperature. The onset of weak ferromagnetism and linear magnetoelectric coupling are shown to coincide with the onset of bulk long‐range magnetic order by neutron diffraction. The synthesis strategy developed here will be invaluable as the phase diagram of BTFM–CTO is explored further, and as an example for the synthesis of other compositionally complex BiFeO3 ‐related materials. Abstract : Phase‐pure bulk samples of the room temperature magnetoelectric multiferroic (1− x )BiTi(1− y )/2 Fey Mg(1− y )/2 O3 – x CaTiO3 are prepared by a synthetic route that balances reaction pathway, starting material reactivity and the loss of volatile Bi2 O3 .